BRACKISH MARSH BENTHIC MICROFAUNA AND PALEOENVIRONMENTAL CHANGES DURING THE LAST 6000 YEARS AT THE COASTAL PLAIN OF MARATHON (SE GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The present study, based mainly on the analysis of foraminifers and ostracodes, provides evidence of paleoenvironmental changes on the coastal plain of Marathon (E. Greece) during the last 6.000 yrs. Three sedimentary units -lagoonal formations - were recognized and identified as A, B and C. They range in time between before 5500BP-3500BP, 3500BP-2500BP and 2500BP-recent, respectively. The study of the brackish marsh microfauna of the Marathon plain Holocene sediments reveals the presence, during the last 5500 yrs., of three distinct biofacies in the sedimentary units already established. Alternating mesohaline - oligohaline (MO), oligohaline - fresh water (OFW) and mesohaline - oligohaline to oligohaline - fresh water (MO-OFW) biofacies in the framework of the sedimentary units indicate a general trend landward along the plain suggesting a slowing of sea-level rise probably correlated with a relevant tectonic uplift. One prominent feature of this study is the clarification of the ecological preference of the species Trichohya1us aguayoi (Bermudez, 1935), which is dominant in oligohaline conditions under an influence of fresh water input (salinity less than 15 ‰).